ISSUES OF GLOBALIZATION AND NATIONAL IDENTITY IN MODERN PHILOSOPHY (British Journal of Global Ecology and Sustainable Development, 2025)
In modern philosophy, issues of globalization and national identity are one of the relevant topics. Globalization processes are leading to increased economic, political and cultural ties between the countries of the world. At the same time, issues of maintaining and developing national identity are also gaining importance. This article analyzes the philosophical aspects of globalization, the concept of national identity and their interaction.